S-asymptotic expansion of distributions - Bogoljub Stankovic (International Journal of Mathematics and Mathematical Sciences)
This paper contains first a definition of the asymptotic expansion at infinity of distributions belonging to G′Rn, named S-asymptotic expansion, as also its properties and application to partial differential equations.